PRODUCTION OF WOOD-BASED COMPOSITES MADE FROM RAPE STRAW WASTES - Kopanskyy , Mykola (Forestry, Forest, Paper and Woodworking Industry, 2014)
The article deals with the analysis of the component structure, the structure of plant material made from rape stems in terms of prospects of their use in the manufacture of particle board or other composite-based materials. It has been presented the basic technological aspects of production of wood-based composite materials using rape raw materials and some of their physical and mechanical property indicators.